Kendali Kecepatan Putaran Motor Smart Wheelchair untuk Meredam Getaran pada Jalan Bergelombang dengan Metode PID - Ganda Wibawa Putra; Dahnial Syauqy; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
A wheelchair is a tool for people who have difficulty walking by foot. There are various types of wheelchairs, one electric wheelchair. In its application, the electric wheelchair users still experiencing inconvenience in the form of vibration is received due to the uncertain road conditions as well as the static motor speed control. Congressional control of the speed of rotation of the Motor the Smart Wheelchair that works by controlling the speed of a DC motor using PID method. Input system of sensors the IMU working as detector uneven road conditions. The results of the readings of the sensors the IMU in the form of the position on the x-axis, y-axis, and z-axis. Input from the sensors the IMU processed on NodeMCU method using the PID to determine the speed of the motor. PID process started off doing the giving the value of the setpoint, and the processing of data from the accelerometer has been transformed into a vector. The input of the sensor will determine the value of the vibration to be processed using the PID. After the output values obtained, electric motors will move in accordance with the magnitude of value of output where the motor can increase the speed up to the highest limit if road conditions. Conversely, if uneven road conditions then the motor will lower the speed up to dampen the shocks. The results of the testing of this system in the form of percentage of IMU sensors sensitivity of 90% and the percentage of the system's success in absorbing the vibrations of 80%.